A rare side effect to pentavalent vaccine - Gore, Rajeshwari S.; Garg, Yashika R.; Jain, Sourabh; Dahiya, Arun (International Journal Of Community Medicine And Public Health, 2016)
A four month old baby experienced itchy reddish raised maculopapular lesions on face, limbs and trunk within 24 hours of immunization with booster dose of pentavalent vaccine. The lesions were not associated with fever, cough, vomiting, or insect bite. There was no similar family history with siblings .There was no history of similar reactions to the previous two doses of the same vaccine. On taking the prescribed medications the lesions subsided in 2-3 days with no recurrence at the time of follow-up.